Harmonisation of Contracts Act 1950 and the Shariah - Nik Mahmod, Nik Ahmad Kamal; Abdul Ghani Azmi, Ida Madieha; Mohd. Sulaiman, Aiman @ Nariman; Engku Ali, Engku Rabiah Adawiah; Daud, Mahyuddin; Abd Ghadas, Zuhairah Ariff (2016)
The Contracts Act 1950 is an ancient piece of legislation that originated from the English common law. Historical records have shown that the introduction of English law through the First, Second and Third Charters of Justice have imported the English law into Malaya. The official introduction of English common law in Malaya was through the application of the Civil Law Ordinance 1938. Contract law was left undisturbed by the English parliament and only when it was brought into India was there legislative effort to codify the law. English contract law has been developed greatly by common law courts to uphold the sanctity of agreements made between men of full age and competent understanding. Contracts are enforced by English courts if they are concluded with free will and consent of contracting parties – the same position which is applicable in today’s modern transactions (Alsagoff, 2003, Chapter 1).